2014
DOI: 10.1155/2014/209753
|View full text |Cite
|
Sign up to set email alerts
|

Dufour and Soret Effects on Square Porous Annulus

Abstract: A study on heat and mass transfer behaviour on porous medium embedded in a square annulus is conducted. The inner surface wall is considered to have a cool temperature T c while the outer surface is exposed to a hot temperature T h. Finite element method (FEM) is used to solve the governing partial differential equations. The results present the influences of the Dufour and Soret effects on the heat and mass transfer of a square annulus. The effects of various physical parameters on the temperature and concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Natural convection in porous medium refers to a case where fluid gets heated due to temperature gradient at different points and moves to areas of lower temperature due to thermal buoyancy. Such studies have been reported for different geometrical and physical parameters of porous fluid combination Yunus Khan et al 2016;Badruddin et al 2007;Prasad et al 1984;Ahmed et al 2011;Zheng et al 2001;Nik-Ghazali. et al 2014).…”
Section: Introductionmentioning
confidence: 87%
“…Natural convection in porous medium refers to a case where fluid gets heated due to temperature gradient at different points and moves to areas of lower temperature due to thermal buoyancy. Such studies have been reported for different geometrical and physical parameters of porous fluid combination Yunus Khan et al 2016;Badruddin et al 2007;Prasad et al 1984;Ahmed et al 2011;Zheng et al 2001;Nik-Ghazali. et al 2014).…”
Section: Introductionmentioning
confidence: 87%
“…Another situation which can arise in practice along with cross diffusions is a chemical reaction produced in the medium. This phenomenon plays an important role in petroleum industry, cooling of nuclear reactors, and packed-bed catalytic reactors [8]. In view of the significance Hayat et al [9] presented the Soret and Dufour effects in threedimensional flow over an exponentially stretching surface with porous medium, chemical reaction and heat source/sink.…”
Section: Introductionmentioning
confidence: 99%
“…The emphasis on the study of natural convection [6][7][8][9][10][11][12][13][14][15][16][17][18], combined radiation and natural convection [19], conjugate heat transfer [20][21][22], and the thermal nonequilibrium approach to investigating heat transfer and fluid flow behavior [23][24][25][26][27] have been reported. In addition to the above, heat and mass transfer [28][29] and heat transfer in square cavities are also discussed in detail [30][31][32][33][34][35][36][37][38][39][40][41][42]. Viscous dissipation is an interesting phenomenon that arises due to friction between the moving fluid and the solid matrix of the porous medium.…”
Section: Introductionmentioning
confidence: 99%